Thermodynamic Analysis of Ammonia Synthesis - Đurić, Slavko (Annals of Mathematics and Physics, 2024)
The paper researches the effect of temperature on ammonia synthesis. The ammonia synthesis reaction N2(g)+3H2(g)=2NH3(g) is exothermic with a negative entropy change. ∆G < 0 condition is fulfilled at lower temperatures up to 464K (Le Chatelierov principle). It is a constant equilibrium of the ammonia synthesis reaction Kp’>>1 at lower temperatures, which means that the NH3(g) synthesis reaction is shifted in the direction of NH3(g) formation (higher production of ammonia). The downside of lowering the temperature is that more ammonia is obtained, but the reaction rate slows down. Above 464K, the free enthalpy of the NH3(g) synthesis reaction is greater than zero, so the reaction enters thermodynamically unfavorable conditions. By increasing the reaction temperature, the ammonia yield NH3(g) decreases in the equilibrium mixture. At 400K, it is 0.5127kmol/kmol (51.27%) and at 700K, the synthesis process NH3(g) is practically complete.